(3TQM GdbGfhf GdJLGQj (B:s (3eUGOQ GdbGfhf GdJLGQj (B-(3GdGYeGd GdJLGQjI(B-(3GdJGLQ GdeJLQ(B-(3GdYbhO GdJLGQjI(B-(3GdJLGQI GdGdcJQhfjI (B. /s - (3SGej, ahRj eMeOs ((3YeGf(B: s (3OGQ GdKbGaI(B, s, 2009)
(3fThA GdbGfhf GdJLGQj h JWhQg , GdJTQjYGJ GdJLGQjI h eUGOQ GdbGfhf GdJLGQj aj GdCQOf , GdGYeGd GdJLGQjI h GdGYeGd GdJLGQjI aj bGfhf GdJLGQI GdCQOfj , GdJGLQ hhGLHGJg , GdSLd GdJLGQj h GdYfhGf GdJLGQj h GdeJLQ , GdYbhO GdJLGQjI HTd YGe , GdQgf GdJLGQj , YbO Gdfbd , GdhcGdI GdJLGjQjI h GdhcGdI HGdYehdI , GdSeSQI , fXQI Ydi GdJLGQI GdGdcJQhfjI h YbO gOg GdJLGQIs
(3eQGLY U(B.349s
Keywords: (3GdJLGQIs; (3GdSLdGJ GdJLGQjIs; (3GdbGfhf GdJLGQjs